2019
DOI: 10.5607/en.2019.28.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Derived from Lactobacillus plantarum Increase BDNF Expression in Cultured Hippocampal Neurons and Produce Antidepressant-like Effects in Mice

Abstract: Gut microbiota play a role in regulating mental disorders, but the mechanism by which gut microbiota regulate brain function remains unclear. Gram negative and positive gut bacteria release membrane-derived extracellular vesicles (EVs), which function in microbiota-host intercellular communication. In the present study, we investigated whether Lactobacillus plantarum derived EVs ( L -EVs) could have a role in regulating neuronal function and stress-induced depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 74 publications
4
111
0
Order By: Relevance
“…2 B) showed the highest abundance (43.8%) in the range between 41 and 60 nm, followed by 20–40 nm (about 20%), and the remaining (about 36%) with a bigger size (between 61 and 140 nm). In spite of the scarce available data, we consider that this size distribution is similar to that reported in literature for bacterial EVs of lactobacilli strains 25 – 28 , specifically for L. plantarum 19 , 29 , whereas the reported range of EVs from pathogenic Gram-positive bacteria seems to be slightly higher, between 10 and 400 nm 6 .
Figure 2 Extracellular vesicles purified from L. plantarum BGAN8 cell-free supernatants.
…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…2 B) showed the highest abundance (43.8%) in the range between 41 and 60 nm, followed by 20–40 nm (about 20%), and the remaining (about 36%) with a bigger size (between 61 and 140 nm). In spite of the scarce available data, we consider that this size distribution is similar to that reported in literature for bacterial EVs of lactobacilli strains 25 – 28 , specifically for L. plantarum 19 , 29 , whereas the reported range of EVs from pathogenic Gram-positive bacteria seems to be slightly higher, between 10 and 400 nm 6 .
Figure 2 Extracellular vesicles purified from L. plantarum BGAN8 cell-free supernatants.
…”
Section: Resultssupporting
confidence: 88%
“…Just to summarize some of the most recent studies, it has been showed that EVs released by probiotics are able to interact with pattern recognition receptors (PRR) of host cells initiating the downstream immune response modulation which, contrary to that induced by pathogens (pro-inflammatory) is more tolerogenic 15 – 18 . Additionally, EVs released by L. plantarum were able to in vivo regulate the brain function being able to reduce the stress-induced depression in mice 19 . Therefore, the EVs released by probiotics, or by the intestinal microbiota, could have multiple applications on human health 6 , 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of probiotic supplementation in the reduction of psychological symptoms [42,43] and as an alternative treatment for CD [25] are nowadays the objects of investigation. Indeed, recent results from clinical trials [44], animal models [45], and in vitro studies [46] indicate that the Lactobacillus administration up-regulates BDNF expression.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of significant shifts, occurring in immune function pathways under spaceflight, vaccination is quite possible and T-cell response is expected to be adequate (Iosim et al, 2019). OMVs could also be potentially employed for treating stress-induced depression of crew members during spaceflight (Choi et al, 2019) or amelioration of metabolic dysfunctions (Ashrafian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of preclinical and clinical evidence supports the concept of bidirectional microbiota-gut-brain interactions ( Mohajeri et al, 2018 ; Toribio-Mateas, 2018 ; Mohajeri, 2019 ), in which OMVs are active players ( Choi et al, 2019 ; Ladinsky et al, 2019 ). In this context, the maintenance of healthy gut microbiota during the interplanetary journeys, e.g., to Mars, will be a challenge in the near future.…”
Section: Introductionmentioning
confidence: 99%